The Impact of Corporate Social Responsibility Practices on Company Reputation in the Manufacturing Sector - Maxel Freydey; Kezia Frigita (IHSA Institute, 2023)
This research investigates the intricate relationship between Corporate Social Responsibility (CSR) initiatives and company reputation within the manufacturing industry. Through a mixed-methods approach encompassing quantitative surveys and qualitative interviews, the study delves into the multifaceted impact of CSR practices on various dimensions of reputation. Findings reveal a robust positive correlation between robust CSR engagement and favorable company reputation across stakeholders, including consumers, employees, and investors. The study underscores the significance of authenticity, transparency, and strategic alignment of CSR efforts with stakeholder expectations in shaping perceptions. Moreover, the research elucidates the relevance of CSR in influencing consumer behavior, driving employee satisfaction, attracting investment interest, and fostering long-term competitiveness. The alignment of findings with established management theories solidifies the theoretical foundations underpinning the CSR-reputation relationship. Recommendations derived from these insights offer actionable strategies for manufacturers to enhance their CSR initiatives, positioning them as socially responsible entities driving positive societal impact while securing a competitive edge in the manufacturing landscape.